2004
DOI: 10.1016/s1525-1578(10)60513-2
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Real-Time Polymerase Chain Reaction Method for Quantitative Analysis of Asparagine Synthetase Expression

Abstract: We established a real-time quantitative PCR (RQ-PCRAsparagine is not an essential amino acid obtained from outside the body because it is synthesized by using the hydrolysis energy of ATP from aspartic acid and glutamine via asparagine synthetase (AS). Even when the asparagine supply is reduced, normal cells can compensate by synthesizing L-asparagine. However, lymphoblastic cells require external asparagine for growth as they lack sufficient AS activity. 1-3 Thus, L-asparaginase is effective against childhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…21 A rapid transcriptional control of the AS gene occurs following deprivation of any single essential amino acid. 6,22 In 1997, Hutson et al 6 demonstrated that depletion of the intracellular asparagine pool by L-Asp was sufficient to activate in vitro AS expression in human leukemic cell lines. The increase in AS mRNA expression also resulted in a simultaneous up-regulation of AS protein levels and AS enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…21 A rapid transcriptional control of the AS gene occurs following deprivation of any single essential amino acid. 6,22 In 1997, Hutson et al 6 demonstrated that depletion of the intracellular asparagine pool by L-Asp was sufficient to activate in vitro AS expression in human leukemic cell lines. The increase in AS mRNA expression also resulted in a simultaneous up-regulation of AS protein levels and AS enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…ASNS expression was measured by RT-PCR in cell lines before and after treatment with ASNase Ā± temozolomide (21, 29). mRNA from a housekeeping gene (18S) was used as an internal standard for the total amount of cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxic effects of ASNase were attributed to asparagine starvation [3,4] and, consistently, low activity of asparagine synthetase (AS), the enzyme that obtains asparagine from aspartate and glutamine, has been considered the most important determinant of sensitivity to ASNase [2,5]. In agreement with this hypothesis, methods have been developed to measure AS expression conveniently, so as to foresee clinical sensitivity to ASNase [6], and several ASNase-resistant cell lines have been characterized that exhibit an increased expression and/ or activity of AS [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%